PENGARUH ASAL DAN UMUR POHON TERHADAP SIFAT PENGERINGAN KAYU SENGON (The effect Age and Location on the drying properties of sengon wood) - Efrida Basri; Syarif Hidayat (Jurnal Penelitian Hasil Hutan, 1993)
This paper discusses the drying properties of sengon (Paraserianthes falcataria) from plantation forest and natural forest. The material used in the study were selected from 5, 15 and 25 year old plantation forest in Jawa Timur, and from natural forest in Maluku. The drying method used in the study were air and solar drying. Wood from plantation forest contain a large portion of juvenile wood which shrink more than the wood from mature wood. As a consequence the wood from plantation forest are more prone to warping.This study reveals that tree age has a significant effect on the drying properties, and wood from natural forest needs more time to dry.Solar drying method are faster up to 40 % of the air drying method.